150 Falls in Malaysia: Magnitude, Risk, Disparities, and Solutions. (20th December 2019) - Tan, Maw Pin; Mat, Sumaiyah; Alex, Deepa; Kamaruzzaman, Shahrul Bahyah
Abstract: The Malaysian Elders Longitudinal Research (MELoR) study found 1 in 4 residents aged 65 years and over living in the Klang Valley of Malaysia fall at least once a year in their survey conducted between 2013 and 2015. Recent figures obtained from the First Older Persons' National Health and Morbidity Survey conducted in 2018 revealed that 15% of Malaysians aged 60 years and over fall at least once a year. In a 10-year follow-up study involving 200 individuals who presented to the emergency department over a six-month period in 2002, 22% were no longer alive at one year, and 80% had died at 10 years. Older age, indoor falls, subsequent hospital admission and functional impairment predicted death at one year. Cross-sectional data from MELoR revealed ethnic differences in fall prevalence, with the ethnic Indians more likely to report falls in the past 12 months compared to the ethnic Malays. Independent risk factors for falls identified from MELoR were urinary incontinence, reduced grip strength, hearing impairment, comorbidities and reducing walking speed. The ethnic differences in falls in our population remain unexplained. Lifestyle and cultural practices may well be the underlying rationale, but genetic influences cannot currently be ruled out. The results of a randomized controlled trial on multifactorial interventions, the Malaysian Falls Assessment and Intervention Trial (MyFAIT), was published last year. Mo differences in falls outcomes with an individualized multifactorial intervention were observed, despite improvements in physical performance and psychological status in the intervention group compared to the control group. The research group has now secured two-year funding to evaluate post-fall behavior in our setting in the Life After Falls (LiAF) study. In addition, dissemination and upskilling efforts are underway through training workshops, formation of the Malaysian Falls Network (MyFalls) and collaborations with the private sector to increase awareness on falls and increase fall prevention efforts throughout the country.